Product Cordial Labeling Of Scale Graph S_1,r(C_3) For r≥3 - Irene, Yanne; Lestari, Winda Ayu Mei; Mahmudi, Mahmudi; Manaqib, Muhammad; Elfiyanti, Gustina (Universitas Wiralodra, 2024)
Graph theory plays a crucial role in various fields, including communication systems, computer networks, and integrated circuit design. One important aspect of this theory is product cordial labeling, which involves assigning labels to the vertices and edges of a graph in a specific way to achieve a balance. Despite extensive research, the product cordial labeling of scale graphs has not been thoroughly explored. This study aims to fill this gap by investigating whether the scale graph can be labeled in a product cordial manner. To achieve this, we followed a three-step methodology: first, we identified the vertices and edge notations of the scale graph ; second, we assigned binary labels (0 and 1) to each vertex and edge to identify a pattern; and third, we proved that this pattern meets the criteria for product cordial labeling. Our findings reveal that the scale graph does indeed support product cordial labeling, thus confirming it as a product cordial graph. This research not only advances our understanding of graph labeling but also provides practical insights that can be applied to optimize network structures and address complex problems in science and engineering.Graph theory plays a crucial role in various fields, including communication systems, computer networks, and integrated circuit design. One important aspect of this theory is product cordial labeling, which involves assigning labels to the vertices and edges of a graph in a specific way to achieve a balance. Despite extensive research, the product cordial labeling of scale graphs has not been thoroughly explored. This study aims to fill this gap by investigating whether the scale graph can be labeled in a product cordial manner. To achieve this, we followed a three-step methodology: first, we identified the vertices and edge notations of the scale graph ; second, we assigned binary labels (0 and 1) to each vertex and edge to identify a pattern; and third, we proved that this pattern meets the criteria for product cordial labeling. Our findings reveal that the scale graph does indeed support product cordial labeling, thus confirming it as a product cordial graph. This research not only advances our understanding of graph labeling but also provides practical insights that can be applied to optimize network structures and address complex problems in science and engineering.